2017
DOI: 10.1016/j.neuroimage.2016.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and expectancy deviations require cortico-subcortical cooperation

Abstract: a b s t r a c tIn a dynamic and uncertain environment it is beneficial to learn the causal structure of the environment in order to minimize uncertainty. This requires determining estimates of probable outcomes, which will guide expectations about incoming information. One key factor in this learning process is to detect whether an unexpected event constitutes a low probability, but valid outcome, or an outright error. The present 7T-fMRI study investigated the role of subcortical structures in regulating this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
4
11
0
Order By: Relevance
“…In contrast, when a novel stimulus is paired with an event already fully predicted based on previously experienced contingencies, no error is generated and no learning about the new stimulus occurs (e.g., Kamin, ; Pearce & Hall, ; Rescorla & Wagner, ; Schultz & Dickinson, ). Researchers have identified the neural underpinnings of such error‐driven learning in both non‐human animals (e.g., Friston, ; Hayden, Heilbronner, Pearson, & Platt, ; Holland & Gallagher, ; Hollerman & Schultz, ; Schultz, Dayan, & Montague, ) and human adults, who also generate prediction errors to violations of learned contingencies (e.g., Behrens, Woolrich, Walton, & Rushworth, ; Brown & Braver, ; Carter et al., ; Fletcher et al., ; McClure, Berns, & Montague, ; Mestres‐Missé, Trampel, Turner, & Kotz, ; O'Reilly, ; den Ouden, Friston, Daw, McIntosh, & Stephan, ; Pessiglione, Seymour, Flandin, Dolan, & Frith, ; Yu & Dayan, ). Evidence suggests that in both non‐humans and humans, dopamine neurons play a key role in signaling prediction error and in driving neuronal and behavioral learning (e.g., Holroyd & Coles, ; Waelti, Dickinson, & Schultz, ).…”
Section: Are Violations Of Core Knowledge Privileged For Learning?mentioning
confidence: 99%
“…In contrast, when a novel stimulus is paired with an event already fully predicted based on previously experienced contingencies, no error is generated and no learning about the new stimulus occurs (e.g., Kamin, ; Pearce & Hall, ; Rescorla & Wagner, ; Schultz & Dickinson, ). Researchers have identified the neural underpinnings of such error‐driven learning in both non‐human animals (e.g., Friston, ; Hayden, Heilbronner, Pearson, & Platt, ; Holland & Gallagher, ; Hollerman & Schultz, ; Schultz, Dayan, & Montague, ) and human adults, who also generate prediction errors to violations of learned contingencies (e.g., Behrens, Woolrich, Walton, & Rushworth, ; Brown & Braver, ; Carter et al., ; Fletcher et al., ; McClure, Berns, & Montague, ; Mestres‐Missé, Trampel, Turner, & Kotz, ; O'Reilly, ; den Ouden, Friston, Daw, McIntosh, & Stephan, ; Pessiglione, Seymour, Flandin, Dolan, & Frith, ; Yu & Dayan, ). Evidence suggests that in both non‐humans and humans, dopamine neurons play a key role in signaling prediction error and in driving neuronal and behavioral learning (e.g., Holroyd & Coles, ; Waelti, Dickinson, & Schultz, ).…”
Section: Are Violations Of Core Knowledge Privileged For Learning?mentioning
confidence: 99%
“…Spatial smoothing of fMRI data is widely adopted at lower field strength to blur inter-subject structural differences in brain anatomy for group analyses, increase statistical power (Turner & Geyer, 2014), and ensure data meets Gaussian Random Field theory assumptions for statistical analysis (Worsley & Friston, 1995). Until recently, many UHF whole brain studies have employed considerable spatial smoothing (Boyacioglu et al, 2014;Goodman et al, 2017;Mestres-Misse et al, 2017). In a recent study, (Torrisi et al, 2018) showed there is a substantial benefit for smoothing the data at 7 T using the same smoothing kernel at 3 T.…”
Section: Spatial Smoothingmentioning
confidence: 99%
“…The challenges of full FOV acquisitions at UHF have resulted in there being a limited number of studies of whole brain function at high spatial resolution to date (e.g., Boyacioglu et al, ; Goodman et al, ; Mestres‐Misse, Trampel, Turner, & Kotz, ; Vu et al, ). In particular there are few studies of cognitive function, as highlighted in a recent review article (De Martino et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial smoothing of fMRI data is widely adopted at lower field strength to blur intersubject structural differences in brain anatomy for group analyses, increase statistical power (Turner and Geyer 2014), and ensure data meets Gaussian Random Field theory assumptions for statistical analysis (Worsley and Friston 1995). Until recently, many UHF whole brain studies have employed considerable spatial smoothing (Boyacioglu, Schulz et al 2014, Goodman, Wang et al 2017, Mestres-Misse, Trampel et al 2017).…”
Section: Spatial Smoothingmentioning
confidence: 99%
“…Only a limited number of publications have studied whole brain functional responses at UHF (e.g. (Boyacioglu, Schulz et al 2014, Vu, Phillips et al 2016, Goodman, Wang et al 2017, Mestres-Misse, Trampel et al 2017)), with the study of cognitive function being limited, as highlighted in a recent review article (De . To date, to our knowledge, only two studies have used UHF fMRI to map responses to complex cognitive tasks in higher-order cortical regions over the whole brain (Vu, Phillips et al 2016, Goodman, Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%